PENGARUH LINGKUNGAN BAHASA ARAB (BI'AH ARABIYAH) DAN POTENSI BAHASA DALAM MENINGKATKAN KETERAMPILAN BERBICARA SANTRI DI PONDOK PESANTREN TERPADU USHULUDDIN - Ramadhani, Syadila; Syaripuddin; Ghazi, Fachrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the influence of the Arabic language environment (Bi'ah Arabiyah) and language potential in enhancing the speaking skills (maharoh al-kalam) of students at the Integrated Islamic Boarding School of Ushuluddin, South Lampung. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results showed that a conducive and structured Arabic language environment significantly improves students' Arabic speaking skills. Additionally, the innate language potential of each student, if developed through appropriate methods and resources, can enhance both oral and written Arabic language proficiency.